Temporal parameters of speech in the hearing-impaired children - Horga, Damir (Array, 2002)
Temporal characteristics of the speech segments of two groups of hearing-impaired children and one group of children with normal hearing and speech status were investigated. The results showed that the speech rate of the hearing-impaired childred was slower than the rate of normal children (21% for mildly hearing-impaired, 43% for deaf children). The duration variability in impaired children was greater. The inherent and the relative duration of the sound categories do not differ significantly between the hearing-impaired and the unimpaired children.